The Effect of the Think, Talk, Write Type Cooperative Learning Model towards Skill of Writing Biographical Text for High School Students - Juliana, Juliana; Idaryani, Idaryani; Pratiwi, Rani Ardesi (JUPE : Jurnal Pendidikan Mandala, 2024)
This study aims to determine the effect of the think, talk, write (TTW) learning model on the writing skills of the tenth-grade students of SMA Negeri 1 Simpang Mamplam. This study uses a quantitative approach with the type of research Quasi Experimental Design using a pretest post-test control group design control design. The population in this study were all students of class X SMA Negeri 1 The population in this study were all students of class X SMA Negeri 1 Simpang Mamplam totaling 91 students. The sample in this study was obtained using the purposive sampling technique, while the sample in this study amounted to 43 students consisting of class X IPA 2 students who were given learning using the conventional model and class X IPS using the TTW learning model. The results of the analysis with the t-test pre-test and post-test experimental class showed a t-value of -16.554 and sig. 0.000. The value of sig states < 0.05 then Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a significant difference from writing a biography of the experimental class using the TTW learning model. Then the results of the calculation of the t-test pre-test and post-test of the control class showed that t was -8.062 and sig. 0.000 and sig states <0.05 then Ho is rejected and Ha is accepted. So, it can be concluded that there is a significant difference from writing from a control class on biographical text and TTW learning model has an effect on the ability to write biographies of students at SMA Negeri 1 Simpang Mamplam.